Cortisol levels in athletes during their adaptation to physical exercise - Shayhelislamova, M.V.; Dikopolskaya, N.B.; Sitdikova, A.A.; Bilalova, G.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to investigate cortisol excretion levels in boys aged 11–15 under conditions of increased physical exertion. Methods and structure of the study. The study involved ice hockey players aged 11–15 and boys from a control group who were undergoing physical training as part of the general school curriculum. The excretion of bound (Cb) and free (Cf) cortisol in urine was studied. The concentration of Cb was determined by chemiluminescent immunoassay on microparticles using the ARCHITECT i optical system (manufactured in the USA). Free cortisol (Cf) was determined using an enzyme-linked immunosorbent assay (ELISA) with the URINARY ‘FREE’ CORTISOL ELISA (EIA-2989) kit (manufactured in Germany). A functional test in the form of a graded bicycle ergometer exercise test was used. Results and conclusions. Increased physical exertion is the dominant factor in the development of glucocorticoid function in the adrenal cortex of boys aged 11–15. High values of Cf and Cb in young ice hockey players, exceeding those of boys in the control group, indicate the stressful impact of physical exertion, particularly in the early stages of the training process. A decrease in Cf at the age of 15 against a background of stable Cb values, observed both at rest and following a controlled physical workload, may indicate the formation of a glucocorticoid reserve during training and an increase in children’s resistance to increased physical workload with age.